Adolescent Bystander Behavior in the School and Online Environments and the Implications for Interventions Targeting Cyberbullying. (2nd October 2017) - Patterson, Lisa J.; Allan, Alfred; Cross, Donna
ABSTRACT: The aim of this study was to add to the emerging knowledge about the role of bystanders in cyberbullying. To differentiate online versus offline bystander behaviors, 292 Australian children (mean age = 15.2; female = 54.4%) reviewed hypothetical scenarios experimentally manipulated by bystander sex, relationship to target and perpetrator, and severity of bullying incident. In both environments, bystander helping behaviors were more likely when the target was a close friend, perceived harm to the target was high, and when bystanders were female. Bystanders also reported being less likely to approach teachers or publicly defend targets in online versus offline environments. This suggests programs designed to encourage positive bystander behaviors online can be similar to face-to-face approaches, but they need to recognize some aspects unique to the online environment.